A emergência da criança no Brasil - Holanda, Fernanda Rosa Borges de (1990)
The aim of this paper is to reflect upon the child in our country who, since the beginings of XIX century, have become the target for forces that took property of her in order to construct the obedient and,above all, profitable individual. The submission to patriarchal power was substituted by submission to an organized and well distributed power inside society which overcomes the bodies and has as strong as discret control over them producing at the end a multitude of individualities and equal ... 'differences ll • Inside the family the woman has occupied a prominent place as far as being the mother - a very important role since then - gives her the responsability for education and formation of children - the future citizens. Her function would be reforced by the school, and other dispositives of the disciplinary power as Foucault understand. Today, the knowledge of child world, the understanding of its necessities, the comprehension of its desires are nothing but a by-product of children control and vigilance practices. To think about these questions is the very begining of the change this paper is to stimulate. By contagion.